Faktor Penentu Minat Investasi di Pasar Modal Syariah: Studi Pada Generasi Z Kota Malang - Bastomi, Mohamad; Nurhidayah, Nurhidayah (Widya Cipta - Jurnal Sekretari dan Manajemen, 2023)
The Islamic capital market has enormous potential to encourage sustainable economic and financial development. Investors in the Islamic capital market are still very small when compared to the total population of Indonesia. Public interest in investing is quite low, but they do not have sufficient knowledge to assess the risks and returns of the Islamic capital market. Thus, the purpose of this study is to examine the factors that influence Gen Z's interest in investing in the Islamic capital market, risk perception, social media influencers, and disposable income. This research utilizes a quantitative methodology focused on the generation Z population in Malang City. A total of 200 research samples were collected using the incidental sampling method. The collected information was analyzed using the PLS (Partial Least Squares) method. The results of data analysis show that interest in investing in Islamic capital markets is influenced by Islamic capital market literacy, risk perception, and social media influencers. However, the results of data analysis show that disposable income does not affect investment interest. This study has practical implications for increasing Gen Z participation in Malang City in investing in the Islamic capital market. Educational efforts aimed at improving Islamic capital market literacy, effective risk management, and utilizing the positive influence of social media influencers can motivate Gen Z's interest in investing in the Islamic capital market.